AGE AND GROWTH OF Hypophthalmichthys molitrix FROM GOBIND SAGAR RESERVOIR (HIMACHAL PRADESH) INDIA - LAL, KRISHAN; DUA, ANISH (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
Gobind Sagar Reservoir was created in 1963, across River Sutlej by constructing a dam at village Bhakra and is situated in Himachal Pradesh, India. Indian Major Carps and exotic carps occur along with other fishes in this reservoir. The exotic carp Hypophthalmichthys molitrix (silver carp) had been introduced accidently in the Gobind Sagar Reservoir in 1971. It has a high fecundity and flourishes very well in this reservoir. Scale samples of H. molitrix from this reservoir were collected from 339 fishes during the period from September 2009 to April 2013.These scales shows annual marks called annuli. Age and growth of this carp were studied by using these scales. Length of the fishes from which the scales were collected was ranged from 23 cm to 87cm. H. molitrix from this reservoir has been estimated to be reaching 44.54 cm during the theoretically calculated harvestable size. It appears to be reaching 47.3 cm after completing three years. At age class 2, length remained 36.19 cm and weight remained 417.21 grams and at age class 3, length remained 47.33 cm and weight remained, 990.31 grams.